Penerapan Prinsip Non Intervensi Dalam Hukuman Mati Terhadap Warga Negara Asing - Wa Djuhardi, Fitri Maryam; Tuhulele, Popi; Daties, Dyah Ridhul Airin (PATTIMURA Law Study Review, 2024)
The ASEAN Charter has clear rules regarding respect for the principle of non-intervention. There is a misunderstanding between the application of the principle of non-intervention and the state responsibility, such as in cases relating to foreign nationals, namely the postponement of the execution of the death penalty against Mary Jane as a Philippine citizen. This raises questions regarding the actions of the Philippine government in handling the problems of its citizens in Indonesia which are considered acts of intervention because they contradict the determination of the death penalty verdict that has permanent legal force. The problems studied include: first, how is the regulation of the principle of non-intervention according to International Law. Second, whether the diplomatic efforts made by the State of the Philippines related to the postponement of the execution of the death penalty against its citizens is an act of violation of the principle of non-intervention. This research uses normative juridical method to find out whether the efforts made by the State of the Philippines is an act of violation of the principle of non-intervention according to International Law. From the research conducted, the conclusion follows that the principle of non-intervention is a principle relating to foreign subjects, meaning that the government must avoid intervening in a country's jurisdiction, but on this side must maintain diplomatic relations. As the Philippine government has done, by submitting appeals, cassations, clemency applications to judicial review. This is the Philippines' responsibility to protect its citizens, while the Indonesian government also has the responsibility to protect national interests. To balance the principle of non-intervention with the interests of cooperative relations in the form of diplomacy can be done by making national policies that have the opportunity to alleviate the death penalty sanctions for certain crimes such as drug crimes.